Column performance of carbon nanotube packed bed for methylene blue and orange red dye removal from waste water - Gill, G.; Mujawar, Mubarak; Nizamuddin, S.; Al-Salim, H.; Sahu, J. (2017)
Environmental issues have always been a major issue among human kind for the past decades. As the time passes by, the technology field has grown and has helped a lot in order to reduce these environmental issues. Industries such as metal plating facilities, mining operations and batteries production are a few examples that involves in the environmental issues. Carbon nanotube is proven to possess excellent adsorption capacity for the removal of methylene blue and orange red dyes. The effect of process parameters such as pH and contact time was investigated The results revealed that optimized conditions for the highest removal for methylene blue (MB) (97%) and orange red (94%) are at pH 10, CNTs dosage of 1 grams, and 15 minutes for each dyes removal respectively. The equilibrium adsorption data obtained was best fit to Freundlich model, while kinetic data can be characterized by the pseudo second-order rate kinetics.